EFFECTIVENESS AND SAFETY OF DIRECT ACTING ANTIVIRAL AGENTS IN THALASSAEMIC PATIENTS WITH CHRONIC HEPATITIS C - Parkash, Arit; Altaf Merchant, Ayesha; Ahmed, Syed Habib; Hussain , Wajid; Hayat, Muhammad Hayat; Memon, Nadeem Ahmed (Journal of Ayub Medical College Abbottabad, 2022)
Background: Pakistan has the highest prevalence of Î’-Thalassemia major in children and Chronic Hepatitis C (HCV) infection is a common transfusion transmitted infection. After the emergence of new generations of Antiviral drugs labelled as Direct Acting Antivirals (DAAs), substantial eradication of HCV has been reported as 90-95% with fewer side effects as compared to older regimen of Peginterferon with or without Ribavirin. The main objective of this study was to assess the Rapid virological response (RVR) at 4th week, End of treatment response (ETR) at 12th week and sustained viral response (SVR) at 24th week achieved by using direct acting antiviral and to assess their safety. Methods: Retrospective descriptive study was conducted from July 2018 to July 2020 at National Institute of Child Health. All Î²-thalassemia major paediatric patients with HCV infection and age between 3-14 years were included. Demographic data, liver function test, HCV PCR, and response of antiviral therapy was recorded and analyzed. Safety was determined by adverse effects reported in records and efficacy was documented by clearance of HCV-RNA to see ETR and SVR. Results: Total 21 patients were treated. Mean age was 7.67±3yr and 12 (57%) were male. Mean weight was 19.3±3.2kg. RVR and ETR was achieved in all (100%) and SVR was achieved in 20/21 (95%) patients. Headache in 2(9.5%) and generalized body ache was found in 1 (4.25%) patient. Conclusion: Combined Sofosbuvir and Daclatasvir were found to be effective and safe for treating HCV in Thalassaemia Major Children.